Konstribusi Wisata Bahari TerhadapMasyarakat Pesisir di Indonesia Dalam Perspektif Sosiologi Maritim - Muhammad Nawir; Egi Regita; Munawati Munawati; Muh Akbar (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to look at the contribution of marine tourism to coastal communities in Indonesia, with a focus on a maritime sociology perspective. Marine tourism is a form of tourism related to activities and destinations centered around the sea or waters. This research utilizes maritime sociology as a relevant perspective for understanding the social life of coastal communities. Maritime sociology is applied as a study involving values, norms and social interactions that are formed through the connection of coastal communities with the sea. The research method uses a qualitative library study approach. Using a literature study approach, this research explores and analyzes various literature sources related to the social impacts of marine tourism in Indonesia's coastal areas. The research results show that (1) Increased social interaction between coastal communities and tourists, creating new dynamics in social relations. (2) The values ​​and norms of coastal communities are influenced, both through cultural exchange with tourists and through adaptation to new values. (3) The social structure is experiencing changes.